PENGEMBANGAN POTENSI ANAK PERSPEKTIF PENDIDIKAN ISLAM - Akhirin Akhirin (Tarbawi : Jurnal Pendidikan Islam, 2015)
One of the main problems in knowing about human beings as learners is a basic nature of human beings when they are born, or so-called potential. Potential in Islam known as nature must be actualized and developed in real life. To develop the potential, the systematic, structured, and planned education based on an interdisciplinary approach and vision in line with the creation of man by God.is needed